Sequential Sampling for Wireworms (Coleoptera: Elateridae) at Sugarcane Planting - Matthew T. VanWeelden; Ron Cherry (EDIS)
In the Everglades Agricultural Area of Florida, where sugarcane is planted on around 410,000 acres annually, wireworms are the most economically important insect pests of newly planted sugarcane. This 3-page fact sheet provides a step-by-step plan to determine whether an application of soil insecticide may be needed to control wireworms. This publication is also a part of the Florida Sugarcane Handbook, an electronic publication of the Agronomy Department. Written by Matthew T. VanWeelden and Ron Cherry, and published by the Department of Entomology and Nematology, August 2016.